A portrait of Carmen: Proudly Kichwa from Saraguro - Pentón Herrera, Luis Javier (2020)
In this work, the author relies on the qualitative portraiture framework and on more than four months of communication to draw Carmen's reality, a Kichwa woman from Saraguro, Ecuador, living in Maryland, the United States. The results of this study draw a little-known reality about Carmen as a trilingual Kichwa immigrant woman who, in turn, is a matriarch of her family, university student, defender, and educator of her children in schools and at home, as well as a bridge of indigenous cultural knowledge for the new generation within their home.